2017
DOI: 10.25115/ejrep.v6i16.1302
|View full text |Cite
|
Sign up to set email alerts
|

Are Phonological Processes Separate from the Processes Underlying Naming Speed in a Shallow Orthography?

Abstract: Introduction. The present study examined the contributions of phonological decoding skills

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
2
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 64 publications
3
2
1
3
Order By: Relevance
“…Intergroup differences in RAN tasks are in accordance with previous studies on transparent orthographies (Lopez-Escribano & Katzir, 2008). RAN results showed strong associations with word recognition and pseudoword speed, so that the impact of serial processing seems to be attributed to the simultaneous activation of visual and phonological representations .…”
Section: Discussionsupporting
confidence: 90%
“…Intergroup differences in RAN tasks are in accordance with previous studies on transparent orthographies (Lopez-Escribano & Katzir, 2008). RAN results showed strong associations with word recognition and pseudoword speed, so that the impact of serial processing seems to be attributed to the simultaneous activation of visual and phonological representations .…”
Section: Discussionsupporting
confidence: 90%
“…Phonological processing develops from phonological ability. Studies have indicated that phonological ability is one of the most powerful predictors of RD in various orthographies (Landerl et al, 2013;Lopez-Escribano & Katzir, 2008). However, in the present study, phonological ability reflected by phoneme segmentation fluency did not predict RD.…”
Section: Discussioncontrasting
confidence: 93%
“…RAN is an important factor related to reading because it requires recalling and naming previously learned stimuli, which is similar to the actual reading behaviour. Our findings are consistent with previous studies in transparent orthographies, such as Greek (Georgiou et al, 2013), Spanish (López-Escribano & Katzir, 2008), Portuguese (Albuquerque, 2012) and Dutch (de Jong & van der Leij, 1999, 2002. López-Escribano and Katzir (2008) indicated that both RAN-number and RAN-letter were associated with the reading performance among Spanish children between 8 and 13 years.…”
supporting
confidence: 95%
“…Our findings are consistent with previous studies in transparent orthographies, such as Greek (Georgiou et al, 2013), Spanish (López-Escribano & Katzir, 2008), Portuguese (Albuquerque, 2012) and Dutch (de Jong & van der Leij, 1999, 2002. López-Escribano and Katzir (2008) indicated that both RAN-number and RAN-letter were associated with the reading performance among Spanish children between 8 and 13 years. In addition, Albuquerque (2012) showed that RAN is a unique predictor of reading and writing performance among Portuguese grade one to grade two students after controlling for the effects of phonics awareness.…”
supporting
confidence: 95%